If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = p + 18 + 5 Reorder the terms: 0 = 18 + 5 + p Combine like terms: 18 + 5 = 23 0 = 23 + p Solving 0 = 23 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 0 + -1p = 23 + p + -1p Remove the zero: -1p = 23 + p + -1p Combine like terms: p + -1p = 0 -1p = 23 + 0 -1p = 23 Divide each side by '-1'. p = -23 Simplifying p = -23
| 2+15=21 | | (-5x-4)-(-2-5x)x=5 | | C*4=8.96 | | Y-x=10-0.5x | | 3m+7m=7 | | 10=2p+4 | | Y=12-6x/-2 | | 8(7-y)=-14 | | C/4=8.96 | | Y-32x+11=0 | | 3a+3z= | | (d+3d)-(-d+2)d=5 | | 7.0x-3x=1 | | 10/(10x-1) | | (6c-4)-(c-3)c=3 | | 8+2n=22 | | 7c-10c+8c-c-c= | | 7a+8=5a-2 | | 2(x-6)-1=5-(4x+2) | | 3h-4h=13 | | 5=17-6t | | B-(2b+1)b=5 | | 8+n=22 | | 4=12-2s | | 20y+9=4(5y+1) | | 5=7-2p | | 2x^5-12x^4+18x^3=0 | | 315/45 | | 2x-46+x=30-7 | | X/4=10.6 | | 9(3-2x)=3(10-8x) | | 0=32x+11 |